Investigations of the effects of sequential tones on the responses of neurons in the guinea pig primary auditory cortex - Scholes, Chris D. (2009)
The auditory system needs to be able to analyse complex acoustic waveforms. Many ecologically relevant sounds, for example speech and animal calls, vary over time. This thesis investigates how the auditory system processes sounds that occur sequentially. The focus is on how the responses of neurons in the primary auditory cortex ‘adapt’ when there are two or more tones.